Tourism Impact of on Beef Cattle Farmers Community in Bilik Sijile Beach, Baluran National Park - Aprylasari, Dede; Azizah, Siti; Man, Norsida (RUAS, 2025)
This research explores the positive and negative impacts of the Bilik Sijile Beach tourism sector on beef cattle farmers' livelihoods and the environment in Merak Hamlet, Baluran National Park. As emerging tourist destinations, these beaches have attracted many visitors, significantly changing the local community. Using a qualitative descriptive approach with SWOT and socio-economic impact analyses, data were collected through in-depth interviews, participant observation, and documentation studies involving 40 purposively selected respondents. The findings indicate positive impacts, including increased business opportunities, income diversification, and improved infrastructure. However, tourism also reduces grazing land quality, environmental pollution, and social changes affecting local traditions. The SWOT analysis highlights strengths like local resources and tourist economic potential alongside opportunities like government support and digital technology advancements. Conversely, weaknesses include technological limitations and resource pressures, while threats encompass market price fluctuations and environmental degradation. This study recommends sustainable tourism development that balances local community welfare and ecological preservation. Integrating environmental conservation with regional economic growth and providing training in tourism management and technology for cattle farmers can enhance adaptation and ensure the sustainability of both tourism and livestock sectors in Merak Hamlet.